2016
DOI: 10.1136/archdischild-2015-309158
|View full text |Cite
|
Sign up to set email alerts
|

Serial C reactive protein values predict sensitivity of organisms to empirical antibiotics in neonates: a nested case–control study

Abstract: Serial CRP values in the first 48 h of antibiotic therapy help to predict whether the causative organism is sensitive to the empirical antibiotics administered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
(10 reference statements)
2
6
0
Order By: Relevance
“…More detailed, serial serum CRP values in the first 48 h of antibiotic therapy help to predict whether the causative organism is sensitive to the empirical antibiotics administered. The suitability of the empirically oriented antibiotic policy could be predicted by a decline in serum CRP within the first 48 h of treatment, which has a high sensitivity and specificity (89% and 80%, respectively) [21]. In addition, the monitoring of serum CRP has an important clinical significance in predicting the prognosis of newborns with sepsis [22,23], which has also been illustrated in our study.…”
Section: Discussionsupporting
confidence: 59%
“…More detailed, serial serum CRP values in the first 48 h of antibiotic therapy help to predict whether the causative organism is sensitive to the empirical antibiotics administered. The suitability of the empirically oriented antibiotic policy could be predicted by a decline in serum CRP within the first 48 h of treatment, which has a high sensitivity and specificity (89% and 80%, respectively) [21]. In addition, the monitoring of serum CRP has an important clinical significance in predicting the prognosis of newborns with sepsis [22,23], which has also been illustrated in our study.…”
Section: Discussionsupporting
confidence: 59%
“…In our cohort none of the infants with sepsis has leukocytosis, and there was no difference between infants with sepsis and normal newborns regarding leukopenia (3% vs. 1.4%, P value = 0.492). Using CRP is not very helpful at the onset of illness [24]. Serial CRP readings have more value [13] which helps in the follow-up of infants at risk who did not receive empirical antibiotics.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a recent study has also demonstrated that serial CRP measurements can predict whether an organism is sensitive to the empirical antimicrobial therapy in the first 48 h of treatment of neonatal sepsis. 38 These findings now need prospective evaluation.…”
Section: Discussionmentioning
confidence: 99%